Analisis Rendahnya Minat Belajar Peserta Didik pada Pembelajaran Bahasa Jawa Kelas IV di Sekolah Dasar - Yuwono, Pratik Hari; Cholis, Agung Nur (Universitas Ma'arif Nahdlatul Ulama Kebumen, 2023)
This study, conducted at SD Negeri Ciberem, aims to identify the factors contributing to the low learning interest of students and describe the teacher's efforts in fostering students' interest in the Javanese language lessons for the fourth grade at SD Negeri Ciberem. Based on the researcher's observations in the fourth-grade Javanese language classes at SD Negeri Ciberem, it was found that students displayed a low interest during learning sessions. This study employs a descriptive qualitative research method. Data collection techniques include observation, interviews, and documentation. The study also involves three sources: teachers, students, and the parents of the students. The study results show that:(1) Factors contributing to the low interest of students in Javanese language learning are rooted in physical and psychological aspects, such as intelligence, attention, and interest. Other influencing factors include teachers, parents, and the learning environment. (2) Teachers' efforts to address students' learning interests include peer tutoring activities, ice-breaking sessions, and adopting a cooperative attitude during instruction. Keywords: Learning interest, Javanese Language, Factors of Leaming Interest, Primary School (SD).